Characterization of a 1 - cysteine peroxiredoxin from big-belly seahorse (Hippocampus abdominalis) ; insights into host antioxidant defense, molecular profiling and its expressional response to septic conditions - Godahewa, G. I.; Perera, N. C. N.; Elvitigala, D. A. S.; Jayasooriya, R. G. P. T.; Kim, G. Y.; Lee, J. (Elsevier, 2016)
1-cysteine peroxiredoxin (Prx6) is an antioxidant enzyme that protects cells by detoxifying multiple peroxide species. This study aimed to describe molecular features, functional assessments and potential immune responses of Prx6 identified from the big-belly seahorse, Hippocampus abdominalis (HaPrx6). The complete ORF (666 bp) of HaPrx6 encodes a polypeptide (24 kDa) of 222 amino acids, and harbors a prominent peroxiredoxin super-family domain, a peroxidatic catalytic center, and a peroxidatic cysteine. The deduced amino acid sequence of HaPrx6 shares a relatively high amino acid sequence similarity and close evolutionary relationship with Oplegnathus fasciatus Prx6. The purified recombinant HaPrx6 protein (rHaPrx6) was shown to protect plasmid DNA in the Metal Catalyzed Oxidation (MCO) assay and, together with 1,4-Dithiothreitol (DTT), protected human leukemia THP-1 cells from extracellular H2O2- mediated cell death. In addition, quantitative real-time PCR revealed that HaPrx6 mRNA was constitutively expressed in 14 different tissues, with the highest expression observed in liver tissue. Inductive transcriptional responses were observed in liver and kidney tissues of fish after treating them with bacterial stimuli, including LPS, Edwardsiella tarda, and Streptococcus iniae. These results suggest that HaPrx6 may play an important role in the immune response of the big-belly seahorse against microbial infection. Collectively, these findings provide structural and functional insights into HaPrx6.
Keywords: Big belly seahorse; Peroxiredoxin 6; H2O2 scavenging; Immune stimulation; Transcriptional responses